The comparison of papilla preservation technique and semilunar incision with sub- epithelial connective tissue graft in dark triangle treatment - Niloofar Jenabian; Morteza Rahimi Rad; Ali Bijani; Pasha Ghahari (Babol University of Medical Sciences, 2018)
Introduction: Ability to reconstruct the papilla in anterior maxilla is important aspect of perio-plastic surgery. In most articles, connective tissue is used with different designs of incisions. The aim of this study was to use sub-epithelial connective tissue graft (SCTG) with two types of incisions called papilla preservation and semilunar. Materials & Methods: This basic randomized clinical study was performed on 10 sites in two patients. The patients were selected through inclusion and exclusion criteria. Papilla preservation and semilunar techniques were performed on four and six sites, respectively in the anterior maxilla. In both techniques SCTG was gained from palate .The apico-coronal and mesiodistal changes of the dark triangles were measured after 3 and 6 months. Landry(Healing) index was measured after 14 days and one month,Visual Analogue Scale (Esthetic) index was estimated in 3 and 6 month after surgery and Visual Analogue Scale (VAS ) index was analysed as well . Data were analysed using SPSS. Mann- Whitney, Wilcoxon and Paired t- Test were measured. Results: Mean±SD of mesiodistal distance in the time of surgery was 2.00±0.000 in semilunar and 2.1±0.629 in papilla preservation technique whereas after 3 months, it was 1.33±0.016 and 1.37±0.478 for semilunar and papilla preservation, respectively and after 6 month was 1.00±0.000 for semilunar and 1.25±0.500 for papilla preservation. Mean±SD of apicocornal changes by semilunar incision in the time of surgery ,3 month after and 6 months later was 2.67±0.516 ,2.25±0.612and1.91±0.204 whereas by papilla preservation was 2.50±0.577,2.25±0.500 and 2±0.000, respectively. Conclusion: Both techniques had positive effect on papilla reconstruction and the outcome was the same in both groups.